Feshbach resonances in the F + H2O → HF + OH reaction - Xiaoren Zhang (Nature Portfolio, 2020)
Feshbach resonances are transiently trapped states along a reaction coordinate, providing a probe to the reaction’s potential energy surface (PES) but difficult to analyze in polyatomic systems. Here the authors identify Feshbach resonances in a reacting 4-atom system by state-to-state quantum dynamics using a full-dimensional PES.